2018
DOI: 10.1073/pnas.1802326115
|View full text |Cite
|
Sign up to set email alerts
|

RNA triphosphatase DUSP11 enables exonuclease XRN-mediated restriction of hepatitis C virus

Abstract: Seventy percent of people infected with hepatitis C virus (HCV) will suffer chronic infection, putting them at risk for liver disease, including hepatocellular carcinoma. The full range of mechanisms that render some people more susceptible to chronic infection and liver disease is still being elucidated. XRN exonucleases can restrict HCV replication and may help to resolve HCV infections. However, it is unknown how 5' triphosphorylated HCV transcripts, primary products of the viral polymerase, become suscepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 37 publications
2
47
0
Order By: Relevance
“…Among the host defense machineries that sense invading pathogens, RIG-I is the key PRR that recognizes the 5 ′ -triphosphate or diphosphate moiety of double-stranded RNA transcripts and in turn activates the antiviral immune defense signaling pathway (Hornung et al 2006). Previous work demonstrated that DUSP11 sequentially removes the γ and β phosphates of triphosphorylated structured host and viral transcripts leaving 5 ′ -monophosphates (Deshpande et al 1999;Burke et al 2016;Kincaid et al 2018). This led us to hypothesize that DUSP11 can modulate the immunogenicity of triphosphorylated transcripts (Burke and Sullivan 2017) and alter the sensitivity of these transcripts to detection by RIG-I.…”
Section: Dusp11 Modulates Rig-i Signaling Sensitivity To Liposomal 5 mentioning
confidence: 99%
See 2 more Smart Citations
“…Among the host defense machineries that sense invading pathogens, RIG-I is the key PRR that recognizes the 5 ′ -triphosphate or diphosphate moiety of double-stranded RNA transcripts and in turn activates the antiviral immune defense signaling pathway (Hornung et al 2006). Previous work demonstrated that DUSP11 sequentially removes the γ and β phosphates of triphosphorylated structured host and viral transcripts leaving 5 ′ -monophosphates (Deshpande et al 1999;Burke et al 2016;Kincaid et al 2018). This led us to hypothesize that DUSP11 can modulate the immunogenicity of triphosphorylated transcripts (Burke and Sullivan 2017) and alter the sensitivity of these transcripts to detection by RIG-I.…”
Section: Dusp11 Modulates Rig-i Signaling Sensitivity To Liposomal 5 mentioning
confidence: 99%
“…We used the 5 ′ untranslated region (UTR) of the HCV RNA, as its expression is immunostimulatory (Saito et al 2007). Additionally, we and others had previously demonstrated triphosphatase activity of DUSP11 on HCV RNAs during infection (Amador-Cañizares et al 2018;Kincaid et al 2018). Consistent with RIG-I induction, cationic-lipid-mediated transfection of HCV 5 ′ -triphosphate RNA (referred to here as "5 ′ -ppp-RNA") into the A549 adenocarcinoma human lung epithelial cell line resulted in the induction of both IFNB1 cytokine and ISG15 mRNA transcripts (Fig.…”
Section: Dusp11 Modulates Rig-i Signaling Sensitivity To Liposomal 5 mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, knockdown of the pyrophosphatases in combination with the 5′ exonuclease (Xrn1) further increased viral RNA accumulation [ 204 ]. These observations were further confirmed by enhanced HCV replication and decreased miR-122 dependency in DUSP11 knockout cells [ 205 ]. Taken together, these results support a model whereby in the absence of the miR-122, DOM3Z and/or DUSP11 can mediate conversion of the 5′ triphosphate of the HCV genome to a monophosphate.…”
Section: Hepacivirusesmentioning
confidence: 81%
“…It is envisaged that HCV RNA genomes have evolved to bind the highly abundant liver-specific miR-122 [9] to guarantee persistence in the liver over many years. Mechanistically, miR-122 has been shown to protect the 5’ ppp-containing HCV genome from the action of 5’ RNA triphosphatase DUSP11 [10, 11] and subsequent degradation by 5’ RNA exonucleases XRN1 [12] and XRN2 [13]. Further evidence suggests that miR-122 also participates in the switch of viral RNAs from the translation to the replication phase in the viral life cycle by displacing of RNA binding proteins that enhance viral mRNA translation [14].…”
Section: Introductionmentioning
confidence: 99%